The Effect of Oxygen Therapy With Nasal Cannula to Oxygen Saturation Through Oximetry Examination For Patients With Heart Failure At Emergency Departmemt of RSUD Ulin Banjarmasin 2018 - Hidayat, Rifky; Aprilia, Hanura (Universitas STRADA Indonesia, 2019)
Background: Heart Failureis a major cause of morbidity and mortality worldwide. In recent years the incidence of HF has increased and the risk of heart failure is increasing all the time. Purpose: To find outthe effect of oxygen therapy by nasal cannula to the oxygen saturation through the examination oximetry in patients with HF in the ER Hospital Ulin Banjarmasin. Method: The study design with pre-experimental design to design one group pretest-posttest design, hearth Failure population all patients with shortness of breath in the emergency room, the study sample using accidental sampling technique. Istrumen using observation sheets, examination using pulse oximetry using univariate and bivariate analysis by paired T-test. Results: The average oxygen saturation before treatment is given after 88.87% and 95.96% obtained by the treatment, an increase in oxygen saturation. There is the influence of oxygen therapy by nasal cannula to the oxygen saturation through the examination oximetry in patients with HF obtained value? value= 0,000 ? ? = 0.05 Conclusion: By giving oxygen therapy, it can increase saturation oxygen for patients with heart failure